Key narratives around agroecological transitions. A systematic literature review of the current debate - Mockshell, Jonathan; Omulo, Godfrey; Hidalgo, Francisco; Quintero, Marcela; Ritter, Thea; Orjuela, Guillermo; Place, Frank (Informa UK Limited, 2025)
As agrifood systems face mounting socio-ecological challenges, agroecology is increasingly viewed as a comprehensive approach to achieving sustainability. However, the public debate over whether this is the most suitable approach or whether it is viable at a large scale remains open. Examining how this debate unfolds is crucial as it can shape the future of agrifood systems. This paper contributes by conducting a systematic literature review to identify key perspectives and actors shaping the public debate around agroecology. Perspectives are framed around three narratives labeled “supportive,” “skeptical,” and “pragmatic.” These narratives are articulated across sub-narratives in six highly debated areas: (1)initial transition costs, (2) input use and supply chain systems, (3) yield potential, (4) labor, (5) scalability, and (6) market access. The review also accounts for a broad group of actors participating in the debate from multiple – sometimes ambiguous and fluid – perspectives. The review shows that mobilizing the debate to enable agroecological transitions requires an integrative approach under-scored by knowledge co-creation and collective learning. Based on insights from participatory approaches, we provide considerations for making these processes work and highlight areas that require further examination